SMALL AND MEDIUM SIZED LIQUID METAL COOLED SAFETY ANALYSIS USING MULTI LEVEL COMPLEXITY MODEL - Zaki Su ud (BATAN, 2008)
SMALL AND MEDIUM SIZED LIQUID METAL COOLED SAFETY ANALYSIS USING MULTI LEVEL COMPLEXITY MODEL Inherent safety characteristics of liquid metal cooled fast reactors is very important capital for next generation nuclear power plants. However inherent safety assessment need appropriate computer code or experiment. Here, a computer code for liquid metal cooled fast reactor accident analysis with various level of complexity has been developed. At the simplest approach, quasi-static method is adopted to get asymptotic condition during UTOP, ULOF, and UTOP-ULOF accident. Here we can get asymptotic power level, asymptotic average coolant temperature, and asymptotic fuel temperature for a certain external reactivity and natural circulation level. In the next grade, the code will simulate transient effect using point kinetic method and quasistatic approach for thermal hidraulic analysis. Here we can get time depedent power change, coolant temperature change and fuel temperature change. Finally in the rigorous analysis, coupled space dependent kinetic and transient thermal hydraulic are coupled and solved to get time depedent information of various process involved in the accident.